MOLLUSCAN DIVERSITY THE MANGROVE ECOSYSTEM OF TARAKAN ISLAND INDONESIA - Nugroho, Bimo Aji; Erisa Ayu Waspadi Putri (BIOMA : Jurnal Ilmiah Biologi, 2024)
Mangrove in Tarakan coast encounter various underlined threat named pollution, habitat destruction, and the swelling of human population impending the existence of Molluscan communities. Molluscan is an essential component of Mangrove ecosystem since it could be as predator, herbivore, detritivore, and biofilter as well. However, there only minimum study found investigate the impact of Mangrove. This study, which was conducted from March to August 2023 in five mangrove regions of Tarakan Island, uncovered the distribution of 54 molluscan species, of which 46 were gastropods and 8 were bivalves. This study has identified a remarkable number of species, among the greatest among mangrove ecosystems in Indonesia. Additionally, this study provides an initial account of the distribution of gastropods in the mangrove region of Tarakan Island. The region north of Tarakan Island known as the Juwata mangrove forest harbors the greatest variety of molluscan. A comprehensive documentation of the molluscan species diversity in the mangrove ecosystem adjacent to Tarakan Island's coast has been compiled in order to furnish conservation management with fundamental data that is practical and beneficial.